Contingency and Event in China's New Documentary Film Movement - Robinson, Luke (Nottingham EPrints, 2007)
This paper addresses the issue of contingency and the event vis-a-vis private and public documentaries. In China, the private and the public documentary form are often understood as mutually antagonistic, with the former defining itself explicitly against the latter. Rather than dwell on these differences, many of which are both well-documented and legitimate, I intend here to demonstrate how in certain ways, the private documentary form may actually be seen as a logical culmination of the xianchang [shooting live] aesthetic initiated by the early pioneers of the New Documentary Film Movement [hereafter NDFM]. In order to do this, I will focus on the issue of the spontaneous event, and its connection with the two documentary forms. After outlining the theoretical relationship between the spontaneous event and the problem of contingency, I proceed to suggest that the early relationship with this aspect of shooting live was in fact highly conflicted, and that the development of the public documentary form was in part a response to such tension. In fact, it was a means of limiting exposure to the contingent as understood in these terms. In the documentary form, such inhibitions have been shed in favour of drawing the contingent event into the heart of the documentary film, something I argue is not in fact restricted to the private genre, but characteristic of a range of contemporary documentary film work. This reflects not only changes in documentary film practice, but also how understandings both of what a documentary is, and what it does, have altered in the decade since the NDFM's inception.